2012
DOI: 10.1177/1362361312459111
|View full text |Cite
|
Sign up to set email alerts
|

Immunization uptake in younger siblings of children with autism spectrum disorder

Abstract: Parents who already have one child with autism spectrum disorder may delay or decline immunization for their younger children, potentially placing them at increased risk of preventable infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…33 There is little information about immunization rates of young children with ASD, although some data suggests that families of children with ASD are more likely to refuse or delay vaccines 34–36 . However, in our study, up-to date immunization prevalence did not differ across ASD, DD and TD groups or predict CAM use.…”
Section: Discussionmentioning
confidence: 99%
“…33 There is little information about immunization rates of young children with ASD, although some data suggests that families of children with ASD are more likely to refuse or delay vaccines 34–36 . However, in our study, up-to date immunization prevalence did not differ across ASD, DD and TD groups or predict CAM use.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of vaccine administration may lead parents to believe that there is a causal relationship between the two. Additionally, parents who already have a child with autism may be even more cautious when vaccinating younger siblings with the MMR vaccine (Kuwaik et al, 2014). The Institute of Medicine committee did not find evidence of a relationship between the MMR vaccine and autism (Maglione et al, 2014).…”
Section: Vaccines and Autismmentioning
confidence: 98%
“…In 2004, 10 of the 13 original authors of the paper recanted their beliefs. The article was officially retracted in 2010 when the British General Medical Council concluded that the researcher had violated the ethics of research by falsifying information and not following appropriate research protocols, which led to his medical license being revoked (Kuwaik et al, 2014;Smith & Marshall, 2010).…”
Section: Vaccines and Autismmentioning
confidence: 98%
See 1 more Smart Citation
“…27 Parent attitudes and beliefs about health are important determinants of vaccine hesitancy. Most common is the belief that vaccines are unsafe and lead to conditions like autism spectrum disorders 28 , which parallel concerns about fluoride. Many parents believe vaccines are no longer necessary.…”
Section: Introductionmentioning
confidence: 99%